Art and Science of the Cellular Mesoscale. Issue 6 (June 2020) - Goodsell, David S.; Olson, Arthur J.; Forli, Stefano
Abstract : Experimental information from microscopy, structural biology, and bioinformatics may be integrated to build structural models of entire cells with molecular detail. This integrative modeling is challenging in several ways: the intrinsic complexity of biology results in models with many closely packed and heterogeneous components; the wealth of available experimental data is scattered among multiple resources and must be gathered, reconciled, and curated; and computational infrastructure is only now gaining the capability of modeling and visualizing systems of this complexity. We present recent efforts to address these challenges, both with artistic approaches to depicting the cellular mesoscale, and development and application of methods to build quantitative models. Highlights: Advances in integration of data and computational infrastructure together are enabling the modeling of large portions of cells, and in some cases, entire cells. Mesoscale models of cellular environments promote research into cellular structure and function by providing thinking tools for hypothesis generation, by providing initial models for simulation and interpretation of experiments, and by providing a new window for the development of drugs. New approaches to visualization and interaction are being developed to address the challenging needs of mesoscale research.